Pengaruh Nilai Wajar, Profitabilitas, Dan Leverage Terhadap Kualitas Laba Pada Sektor Perbankan - Rifdah Aristawati; Raissa Putie Imaniyah; Adistinur Syafira; Agustine Dwianika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Profit is the most important thing for a company because it is a benchmark when making decisions. If the higher the profit generated, the quality of the profit is also of high value. Profit is also one of the most important benchmarks for measuring an organization's financial performance, such as in the banking context. This study aims to examine the effect of fair valuation, profitability, and leverage on earnings quality in banking sector companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The data source used in this study is a secondary data source, namely financial reports which include the company's annual financial statements as of December 31 for the 2017-2021 period obtained from the official website of the Indonesia Stock Exchange (IDX) or from the website of each company. The samples used were 10 banking companies using a purposive sampling method. The data is processed using SPSS 26. The results of this study indicate that fair judgments affect earnings quality. Meanwhile, profitability and leverage have no effect on earnings quality.